Penerapan Model Scramble Dalam Pembelajaran Membaca Bahasa Mandarin Pada Siswa Kelas IV SD Frater Thamrin Makassar - Sulfani Baso; Nurming Saleh; Himala Praptami Adys (Universitas Negeri Makassar, 2021)
This study is classroom action research (CAR). The aim of this the process of planning conducted, and implementing the scramble model in reading Mandarin at fourth graders student of Frater Thamrin Elementary School of Makassar. The subjects of this study were 20 students of fourth graders at Frater Thamrin Elementary School. Data were collected through observation and Mandarin reading tests. And were with presentation analyzed. The results of this study showed of the students in the first cycle is 67.87% and in the second cycle is 90.87%. so it can be conculed that, the implementation of scramble model improves the reading ability the students of graders fourth student at Frater Thamrin Elementary School of Makassar.Keywords: Application, Scramble, Reading, Mandarin.